Undiagnosed hypoglycaemia disorders in children detected when hypoglycaemia occurs in the setting of illness: a retrospective study - Diva D De León; Elizabeth Rosenfeld; Ohoud Alzahrani (BMJ Publishing Group, 2023)
Objective Whether hypoglycaemia incidentally detected during intercurrent illness in children requires an endocrine workup remains controversial. This study aimed to determine the yield of conducting a diagnostic evaluation in this setting and to compare clinical and biochemical features between patients ultimately diagnosed with a hypoglycaemic disorder and those who were not.Design Single-center, retrospective review of children referred to endocrinology between January 2013 and December 2018 for evaluation of hypoglycaemia (defined as plasma glucose<3.9 mmol/L (<70 mg/dL)) in the setting of acute illness.Results 145 patients met eligibility criteria. A hypoglycaemia disorder was identified in 12 patients (8% of the cohort, 17% of those who underwent a diagnostic fast). There were no cases in which diagnosis was established in the absence of a diagnostic fast. Characteristics associated with identifying an underlying disorder included younger age (1.03 years (IQR: 0.05-1.54) vs 2.18 years [IQR: 1.29-3.99], p<0.001), higher bicarbonate level (22±5.5 mmol/L vs 16±3.6 mmol/L, p<0.001), lower frequency of elevated plasma or urine ketones (25% vs 92%, p=0.004) and lower frequency of other documented medical problems (17% vs 50%, p=0.03).Conclusions The yield of diagnostic evaluation among children with incidental detection of hypoglycaemia in the setting of illness is not insignificant. We thus recommend that all children with hypoglycaemia in the setting of illness undergo guided diagnostic evaluation. Younger age and absence of ketosis and acidosis at presentation may serve as useful predictors for establishing a diagnosis. Future studies are needed to confirm these findings.